MMPI analysis of 12345 convenience hotline operators - Ma, Lin; Tong, Yongsheng; Wang, Tongtong; Zhang, Dong; Yang, Xingjie; Xu, Haiting; Liu, Xiao (Frontiers in Psychiatry, 2025)
ObjectiveThis study aimed to assess 12345 Government Service and Convenience Hotline operators using the Minnesota Multiphasic Personality Inventory (MMPI), with the goal of identifying their personality traits and psychological characteristics. Drawing on these findings, constructive recommendations were proposed to improve the operators’ mental well-being, thereby enhancing the overall quality of their service provision.MethodsA total of 971 operators from the government service and convenience hotline in City B were recruited as participants. The Minnesota Multiphasic Personality Inventory (MMPI) was used to assess the participants’ psychological characteristics.ResultsThe overall rate of abnormal psychological characteristics was 76.1%, with 28.53% showing mild abnormalities, 11.12% moderate abnormalities, and 36.46% severe abnormalities. Repression was the only subscale with the mean score exceeded the borderline normal threshold (T >60), and fewer than 50% of participants scored within the borderline normal range. There were significant differences in five aspects of hypomania: Hypomania, Correction, Dependence, Social Responsibility, and Bias between operators with moderately and severely abnormal mental status and those with normally and mildly abnormal mental status (p < 0.001). The results of multiple subscales of male operators were significantly different from those of female operators (p < 0.05).ConclusionThe mental status of 12345 public service hotline operators was found to be suboptimal, with high prevalence of occupational burnout. Operators with moderate - to - severe abnormal mental status faced limited psychological resources, which hindered their professional performance. This study also identified gender-based differences in the mental status of 12345 hotline operators. Male and female hotline operators each possess distinct strengths in hotline service delivery. Training supervisors to recognize the early signs of burnout is not only important but also meaningful, as it helps ensure the smooth operation of 12345 Government Service Hotline services.